Sustainable and simple processing technique for n-type skutterudites with high ZT and their analysis. (July 2019) - Rogl, Gerda; Yubuta, Kunio; Kerber, Michael; Grytsiv, Andriy; Zehetbauer, Michael; Bauer, Ernst; Rogl, Peter
Abstract: As various branches of industry are interested in good thermoelectric generators, there is a serious demand for an easy, fast, cheap and sustainable production route of excellent thermoelectric materials. In this paper we demonstrate how we could achieve a high-ZT (ZT ∼ 1.45 at 823 K) n-type bulk skutterudite, (Mm, Sm)y Co4 Sb12, by processing the industrially produced raw powder using a modified high-pressure torsion (HPT) equipment at elevated temperature under inert gas. For this HPT processed sample as well as for the annealed one, structural properties, especially focused on grain size and dislocation density (backed up by electron probe microanalysis, transmission electron microscopy investigations as well as XPD profile analysis), physical properties (from 300 to 823 K and for the electrical resistivity in addition from 4.2 to 300 K) and mechanical properties (elastic moduli, hardness, fracture resistance) were measured and evaluated and compared with the values of a traditionally prepared bulk material, using hot pressing (HP). As a consequence of severe plastic deformation, we found a change from metallic to semiconducting behavior during measurement induced annealing of the HPT processed skutterudite, which could be explained via the change of lattice distortion and its influence on the band gap. A positive ZT net effect occurred because although the electrical resistivity was enhanced the thermal conductivity was decreased. It turned out that the elastic moduli of the HPT samples were not much different from those of the HP skutterudite, however, that the hardness was significantly increased. Graphical abstract: Image 1